BENTUK-BENTUK PELANGGARAN PRINSIP KESOPANAN DALAM CERAMAH KEAGAMAAN - Kusno, Ali; Rahman, Abd. (LiNGUA: Jurnal Ilmu Bahasa dan Sastra, 2016)
religious lecture is the effective means of propaganda for direct interacting to the worshipers. Unfortunately, there are some lecturers who do not pay attention to the politeness principle in the preaching. One lecturer who often causes controversy is GN. GN lectures on several occasions, such as lectures in churches, sparked debate and a negative response from the other speaker. This research is to reveal the forms of principle courtesy violation in discourse. This research used descriptive qualitative research with discourse analysis approach. The analysis showed the forms of the offense of direct criticism (menohok hearer) with a word or phrase that is abusive, speech-driven sense of emotion, intent cornered hearer, the charges on the basis of suspicion, protective of opinions, attack the personal aspect, and the spread of hatred. The forms of violations that included part of the Approbation Maxim. It can be concluded that the conflict (linguistic and social) can be triggered by a lecture, disregarding the principle of modesty. Linguistic conflict, like debate between lecturers, would arise not because of the debate the substance of propaganda, but the attack triggered a personal aspect and spreading hatred. Conflicts are likely to occur when the violation of the principle of courtesy is still ongoing. The negative impact of the conflict would be stronger if it involves an object or group of people with different religious and ethnic.